Estimation of cAMP binding in hippocampus CA1 field by a fluorescent probe - Mucignat-Caretta, Carla; Caretta, Antonio (Frontiers in Cell and Developmental Biology, 2023)
The hippocampus is an allocortex structure involved in many complex processes, from memory formation to spatial navigation. It starts developing during prenatal life but acquires its adult functional properties around the peripubertal age, in both humans and mice. Such prolonged maturation is accompanied by structural changes in microcircuitry and functional changes involving biochemical and electrophysiological events. Moreover, hippocampus undergoes plasticity phenomena throughout life. In murine rodents, the most relevant maturation steps in Cornu Ammonis 1 (CA1) hippocampal subfield occur during the third-fourth weeks of life. During this period, also the expression and localization of cAMP-dependent protein kinases (PKA) refines: many regulatory (R1A) PKA clusters appear, bound to the cytoskeleton. Here the binding characteristics of R1A are determined in CA1 by using confocal microscopy. Apparently, two binding sites are present with no evidence of cooperativity. Equilibrium dissociation constant is estimated around 22.9 nM. This value is different from that estimated for R1A in soluble form, suggesting a different binding site conformation or accessibility in the tissue. The method described here may be useful to track the developmental changes in binding activity, which affects cAMP availability at selected intracellular microzones. Possible relations with functional consequences are discussed.